Fruit and Leaf Sensing for Continuous Detection of Nectarine Water Status - Scalisi, Alessio; O’Connell, Mark Glenn; Stefanelli, Dario; Lo Bianco, Riccardo (Frontiers in Plant Science, 2019)
Continuous assessment of plant water status indicators provides the most precise information for irrigation management and automation, as plants represent an interface between soil and atmosphere. This study investigated the relationship of plant water status to continuous fruit diameter (FD) and inverse leaf turgor pressure rates (pp) in nectarine trees [Prunus persica (L.) Batsch] throughout fruit development. The influence of deficit irrigation treatments on stem (Ψstem) and leaf water potential, leaf relative water content, leaf stomatal conductance and fruit growth was studied across the stages of double-sigmoidal fruit development in 'September Bright' nectarines. Fruit relative growth rate (RGR) and leaf relative pressure change rate (RPCR) were derived from FD and pp to represent rates of water in- and outflows in the organs, respectively. Continuous RGR and RPCR dynamics were independently and jointly related to plant water status and environmental variables. The independent use of RGR and RPCR yielded significant associations with midday Ψstem, the most representative index of tree water status in anisohydric species. However, a combination of nocturnal fruit and leaf parameters unveiled an even more significant relationship with Ψstem, suggesting a changing behaviour of fruit and leaf water flows in response to pronounced water deficit. In conclusion, we highlight the suitability of a dual-organ sensing approach for improved prediction of tree water status.